The real-time predictive content of asset price bubbles for macro forecasts - Benjamin Beckers (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
In light of the recent large swings in stock and housing prices accompanied by ample global liquidity, the role of monetary policy in the build-up of asset price bubbles has been questioned. This paper will contribute to the debate whether central banks can and should stronger "lean against the wind" of emerging bubbles. Against this background, the paper will reevaluate if new advances in real-time bubble detection, as brought forward by Phillips et al. (2011), can timely detect bubble emergences and collapses. Here, the paper suggests a combination approach of different bubble indicators to account for the uncertainty around start and end dates of asset price bubbles. Additionally, the paper will then investigate if these indicators carry predictive content for inflation, output growth and recession events when the real-time availability of all variables is considered. It finds that a combination approach of asset price bubbles is well suited to detect the most common stock and house price bubbles in the U.S. and shows that this indicator can improve output forecasts, however, only when the real-time availability of real variables is respected.
Keywords: C53; E44; G12; 330